Photo Racemization and Polymerization of (R)-1,1′-Bi(2-naphthol) - Zhaoming Zhang; Yue Wang; Tamaki Nakano (Molecules, 2016)
(R)-1,1’-Bi(2-naphthol) ((R)-BINOL) in an acetonitrile solution lost optical activity upon irradiation with an Hg–Xe lamp. HPLC resolution of the product indicated that (R)-BINOL was racemized upon irradiation, and SEC analysis suggested that a polymeric product was formed in the course of racemization. It is proposed that polymerization of BINOL can occur before it is racemized and that a unit in a polymer derived from BINOL may lose its optical activity afterwards due to in-chain racemization and/or reduction. The polymeric products seem to consist not only of BINOL residues but also of residues derived from acetonitrile as well as those derived through reduction of BINOL.